Pemanfaatan Biji Kakao dalam Pembuatan Olahan Selai Cokelat - Dinda Nadhifah Aprillia; Prayoga Suryadarma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
There are a lot of agriculture businesses in Indonesia, but there is no maximum utilization of economic waste from cacao beans and that is of economical value. Cacao beans be produced should not be used as raw materials that are directly sold but can be additional products that have high economic value if processed properly. The purpose of this study is to determine the use of cocoa beans into chocolate jam that supports the efforts of farmers in the village Sidomulyo, Kecamatan Lebak barang, Pekalongan Regency. The method used in this study is the first stage, namely the preparation of fermented and unfermented (drying) cocoa beans and the interview method. Based on the experimental results, it was found that the cocoa butter processed from roasted unfermented cocoa beans had better quality than the cocoa butter prepared from roasted fermented cocoa beans and chocolate jam using 2 tablespoons of cocoa powder had very good aroma and flavor. Keywords : Cacao Beans, Chocolate Jam, Drying.